Acute Toxicity Pattern In 3d-Crt Versus Imrt For Locally Advanced Oral Cavity Cancer - Siddiqui, Hiba; Lakhan, Abdul Hafeez; Badar, Qurat-ul-Ain; Ashraf, Farrukh; Khan, Asma; Mallick, Jawaid (Journal of Rawalpindi Medical College, 2026)
Objective: Locally advanced oral cavity cancers (OCC) present substantial treatment challenges, requiring radiotherapy as a primary intervention. Although intensity-modulated radiation therapy (IMRT) provides better dose precision than 3D conformal radiotherapy (3D-CRT), their acute toxicity differences, notably mucositis, dysphagia, and dermatitis, are crucial for optimizing patient outcomes, particularly in regions where advanced-stage disease is prevalent and resources are limited. Methods: This prospective comparative study enrolled 110 postoperative OCC patients (55 per arm) receiving adjuvant IMRT or 3D-CRT (66–70 Gy). Patients were assessed weekly during treatment until the end of radiation treatment and at 2nd, 4th, and 6th week post-treatment using NCI-CTCAE v4.03 criteria to assess radiation-induced mucositis, dysphagia, and dermatitis. Exclusion criteria included concurrent chemotherapy or prior radiotherapy. Statistical analysis employed chi-square tests (SPSS v20; significance: p < 0.05). Results: During the treatment phase, the incidence of mucositis, dysphagia, and radiodermatitis was comparable between the 3D-CRT and IMRT arms. In the post-treatment period, however, the IMRT arm demonstrated a more rapid resolution of acute toxicities. At 4 weeks post-RT, the proportion of patients with grade 3 mucositis was significantly lower with IMRT compared to 3D-CRT (4.1% vs. 48.8%, p = 0.0001). Dysphagia severity was greater in the 3D-CRT arm, with grade 3 dysphagia observed in 62.5% versus 28.6% of patients at week 7 (p = 0.003). Although radiodermatitis grades were similar post-treatment, recovery was faster in the IMRT group, with grade 1 radiodermatitis at 6 weeks post-RT in 75% versus 24.4% of patients in the 3D-CRT arm (p = 0.0001). Conclusions: IMRT significantly reduces post-treatment toxicity burden, with higher resolution of mucositis, dysphagia, and dermatitis compared to 3D-CRT. These findings underscore IMRT’s clinical advantage in improving patient recovery and quality of life, advocating for its prioritized use in locally advanced OCC. Keywords: Oral cavity cancers, Radiotherapy, Conformal, Dysphagia, Radiodermatitis.